2021
DOI: 10.1001/jamacardio.2021.2821
|View full text |Cite
|
Sign up to set email alerts
|

Myocarditis Occurring After Immunization With mRNA-Based COVID-19 Vaccines

Abstract: Two reports in the current issue of JAMA Cardiology describe cases of acute myocarditis that occurred among persons who received the BNT162b2-mRNA (Pfizer-BioNTech) or mRNA-1273 (Moderna) messenger RNA (mRNA)-based COVID-19 vaccines authorized for use in the US. 1,2 During the clinical evaluations of these patients, alternative etiologies for myocarditis were not detected.The first report describes 4 cases of myocarditis with symptom onset 1 to 5 days after receipt of a second dose of mRNA-based COVID-19 vacci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
88
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(99 citation statements)
references
References 11 publications
7
88
0
Order By: Relevance
“…Acute myocarditis following vaccination is a rare but serious complication, which has until now been recognized as associated almost exclusively with smallpox and influenza immunization [2]. Myocarditis in the course of COVID-19 infection was previously described [3,4]; however, only recently have the first cases of acute myocarditis following administration of the mRNA-based anti-COVID-19 vaccines (Pfizer-BioNTech and Moderna) been reported [2,5]. This complication typically occurs in young adult males within 4 days after administration of the second dose of the COVID-19 vaccine [2,5].…”
mentioning
confidence: 99%
“…Acute myocarditis following vaccination is a rare but serious complication, which has until now been recognized as associated almost exclusively with smallpox and influenza immunization [2]. Myocarditis in the course of COVID-19 infection was previously described [3,4]; however, only recently have the first cases of acute myocarditis following administration of the mRNA-based anti-COVID-19 vaccines (Pfizer-BioNTech and Moderna) been reported [2,5]. This complication typically occurs in young adult males within 4 days after administration of the second dose of the COVID-19 vaccine [2,5].…”
mentioning
confidence: 99%
“…Several cases of myocarditis have been reported in the period shortly after a Covid-19 vaccination but were deemed to have a different underlying cause. [6,7] In our case, all the tests performed in search of an infectious or immune-mediated cause proved negative, and serological testing demonstrated a typical pattern of SARS-CoV-2 immunization.…”
Section: Resultsmentioning
confidence: 49%
“…However, ongoing surveillance has suggested that COVID vaccines may be associated with thrombosis with thrombocytopenic syndrome (TTS) [39][40][41] or myocarditis. 42,43 These adverse events have varied by the specific vaccine administered. However, the benefits of vaccination clearly remain greater than rare serious side effects.…”
Section: Remaining Pandemic Concernsmentioning
confidence: 99%